Designing History-Based Educational Games to Improve Cognitive Empathy in Children with ASD: A Pilot Study - Cai Gi; Nanang Hoesen Hidroes Abbrori (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Children with Autism Spectrum Disorder (ASD) face significant challenges in Theory of Mind (ToM), particularly in understanding others' perspectives. While serious games have shown potential, most existing interventions focus on basic emotion recognition without engaging narrative contexts. Objective: This pilot study aims to design a history-based serious game, "Tarumanegara Adventure," and evaluate its preliminary effectiveness in improving cognitive empathy among children with high-functioning ASD. Using a mixed-methods case study approach with a one-group pretest - post-test design, six students with ASD (aged 8-15) participated in a 2-week intervention. The game integrates historical narratives as a logical scaffold with explicit emotion scaffolding and moral decision-making mechanics. Data were analyzed using the Wilcoxon Signed-Rank Test and triangulated with behavioral observations. Quantitative results showed a significant increase in cognitive empathy scores (p = 0.0312) with a large effect size (Cohen’s d = 3.19). However, triangulation revealed a "knowing-doing gap," in which higher cognitive scores did not correlate significantly with spontaneous prosocial behavior (ρ = -0.36). Conclusion: The history-based narrative approach effectively enhances cognitive knowledge of empathy by providing a structured context. However, bridging the gap between cognitive understanding and spontaneous behavioral application remains a critical challenge for future game design.